Insecticides Agriculture and Toxicology - Begum, Ghousia (IntechOpen, 2018)
Insecticides are substances used to kill insects. They are used primarily in agriculture to control pests that infest crop. Nearly all insecticides have the potential to significantly alter ecosystems: many are toxic to humans and/or animals; some become concentrated as they spread along the food chain. The presence of these chemicals in both aquatic and terrestrial ecosystems has become an important issue globally. The book Insecticides - Agriculture and Toxicology provides information on the use of insecticides in pest management in order to enhance crop protection and their effects on nontarget organisms.